The crystal structure of (Z)-2-(tert-butyl)-6-(7-(tert-butyl)-5-methylbenzo[d][1,3]oxathiol-2-ylidene)-4-methylcyclohexa-2,4-dien-1-one, C23H28O2S - Zhang Qiumei; Xu Mingming (Zeitschrift für Kristallographie - New Crystal Structures)
C23H28O2S, monoclinic, P21/m (no. 11), a = 9.3198(3) Å, b = 7.0131(2) Å, c = 15.4566(4) Å, β = 106.236(3)∘, V = 969.96(5) Å3, Z = 2, Rgt(F) = 0.0335, wRref (F2) = 0.0922, T = 100 K.